Participação e representatividade como uma boa prática de governança em cooperativas de crédito: estudo de caso de núcleos do programa sicredi pertencer - Bordin, Marina da Silva (Universidade do Vale do Rio dos Sinos, 2016)
This study is meant to examine the good governance practices, participation and representativeness of members in surveyed core groups, and from the results propose actions. The research method chosen in this descriptive and exploratory research is a case study with a quantitative approach, through a questionnaire answered by 674 members of the Sicredi Pertencer Program. The questions were defined from seven categories, which resulted from the theoretical framework: profile; call notice, the meeting and the minute; voting and election; documents for deliberation; education for members; participation; representativeness. The survey answers were imported into IBM SPSS software in order to generate tables, and perform hypothesis testing. It was used the descriptive statistics, namely the determination of frequencies, percentages, means and standard deviations. In order to identify correlations among variables, it was used the chi-square, with significance level (p = 0.05), and to determine the difference among the average response in two variables, it was used the test-t, with level of significance (p = 0.05). From the analysis of the survey results for each category, it was observed that there are significative differences among the core groups, which made the improvement opportunities being able to be directed, that explained the core groups most in need of development. Two suggestions from this work have already been implemented: the construction of the profile of the Core Groups of Sicredi and the development of the Core Group Meter (a tool to support the Core Group’s leader to play its role and to engage members in the meetings to participate actively in the Credit Union’s development). Two suggestions are being reviewed: using CRM as a driver of good governance practices and the introduction of the concept of Core Group Turnover, aiming to make efforts to the members, whom already have a good relationship level (use of goods and services) with the credit union, but have not yet participated in any meeting with members, to participate in at least one meeting. The survey also found that unions have the opportunity to improvement to give access and create opportunities for member’s participation, because most of the time, they tend to take benefit from the good practice implemented. It was not possible to secure the chances of neither the old Cooperative members being more participative nor the members from smaller cities.
Keywords: Cooperativismo; Governança; Boas práticas de governança; Participação; Representatividade; Cooperativism; Governance; Good governance practices; Participation; Representativeness; ACCNPQ::Ciências Sociais Aplicadas::Administração